Restorative Justice in Resolving Juvenile Crimes in Indonesia - Rayhan, Muhammad (Journal of Law and Humanity Studies, 2024)
In the juvenile criminal justice system in Indonesia, the restorative justice approach is an alternative that is increasingly prioritized compared to the retributive justice system which tends to punish children without considering the psychological and social impacts. Restorative justice emphasizes the restoration of relationships between perpetrators, victims, and the community with the aim of rehabilitation and social reintegration of children who are facing the law. Although it has been supported by regulations such as Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law), the implementation of restorative justice still faces various obstacles, such as lack of understanding by law enforcement officials, community resistance, and coordination challenges between institutions. This study aims to analyze the effectiveness of the implementation of restorative justice in the settlement of juvenile crimes in Indonesia and explore the challenges and opportunities in its implementation. The method used is a literature study with a systematic literature review (SLR) approach, which includes the analysis of various journal articles, books, and laws and regulations related to the juvenile criminal justice system in Indonesia. The results show that the restorative justice approach is able to reduce the level of child recidivism, increase the involvement of victims in case resolution, and minimize the negative impact of the judicial process on child development. However, the success of this approach still depends heavily on the support of the law enforcement authorities, the role of the community, and adequate rehabilitation infrastructure. Therefore, a more systematic strategy is needed to strengthen the implementation of restorative justice to create a fairer and rehabilitation-oriented juvenile justice system.